Job Search Methods and Outcomes - John T. Addison; Pedro Portugal (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
In this paper we investigate the process of job search, using a unique, large-scale data set for Portugal that allows us to assess the effect of job search methods on escape rates from unemployment and, in a new departure, the impact of job-finding methods used by the unemployed on earnings. In each case, the characteristics of workers receive careful attention. In addition, the effectiveness of the job search process is evaluated in terms of the periodicity of the resulting job match. Some emphasis is accorded the role of the public employment agency which, despite its frequency as a search vehicle, is found to have a low hit rate and to lead to low-paying jobs. Such jobs are also shorter lasting, only partly because they are more likely to be of a fixed-term nature. The policy backdrop is provided by the "employment chapter" of the Treaty of Amsterdam. Given our results, some concern naturally arises as to the capacity of the public employment agency to meet the targets set under European employment initiatives.
Keywords: 330; Arbeitsuche; Arbeitslosigkeit; Dauer; Schätzung; Portugal